Essential oils and hydrolats of oregano and clove on the mycelial development of Botrytis cinerea isolated from strawberries - Drawanz, Bruna Bento; Bueno, Thalles da Rosa; Bocchese, Carla Azambuja Centeno; Bez, Felipe Suzin; Antunes, Luidi Eric Guimarães (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The aim of this work was evaluated essential oils and hydrolats of O. vulgare and S. aromaticum, extracted by hydrodistillation, from its abilities to control mycelial growth of the fungus B. cinerea (gray mold) isolated from Albion strawberries as alternative management, ecological and sustainable to combat the disease. The inhibition of mycelial growth was evaluated in the treatments: 5, 15 e 30% for each hydrolats and 10% for each essential oil. There was no considerable fungal activity in the first 24 hours of experiment. The hydrolates are active in 48 hours at the lowest concentration (5%) with mycelial growth inhibition percent (GIP)= 94% (O. vulgare) and 84% (S. aromaticum). Hydrolats at 15% maintained the MGIP above 90% for up to 72 hours not differing statistically from 48 hours of monitoring. Hydrolats 30% treatments, the GIP was 100% all period and did not differentiate statistically between treatment days. Both essential oils differed statistically from the control after 48 until 96 hours. The O. vulgare oil was more efficient with GIP =100% for the entire experiment and the S. aromaticum oil, in 48 hours, a GIP =64% that remained until 96 hours. The study demonstrated the antifungal action against B. cinerea of all-natural extracted product tested, aqueous and oily.